Coronectomy of mandibular third molars: A clinical protocol to avoid inferior alveolar nerve injury. Issue 8 (October 2015) - Monaco, Giuseppe; Vignudelli, Elisabetta; Diazzi, Michele; Marchetti, Claudio; Corinaldesi, Giuseppe
Abstract: Coronectomy is a surgical procedure for the treatment of mandibular third molars in close proximity to the mandibular canal. Unfortunately, often the surgical protocol is not described step by step and it is difficult for the clinician to assess the key factors that are important for the success of this procedure. The aim of this paper is to propose and describe a standardized surgical protocol to improve the success of the technique. The treatment approach, for the most common types of third molars impaction is analysed. Each step of the surgical procedure is described in details and a new type of crown section is proposed. The presented protocol is proposed in order to define a clinical practitioner's guide that could help the surgeon who approaches coronectomy for the first times.